Pembelajaran Seni Musik Dengan Media Pianika Terhadap Siswa Tunarungu - Manurung, Elvita Turema; Ichwan, Clemy Ikasari; Hermawati, Sri (Program Studi Pendidikan Musik, 2023)
Abstract: The purpose for this research is for knowing the learning of music with piano media for deaf students at SDLB/B Pangudi Luhur. When the research was carried out from November to December 2020 offline. The object of this study is learning the art of music with piano media at SDLB/B Pangudi Luhur. The research method used in this research is descriptive qualitative. Data collection through observation, interviews with sources and experts, as well as written sources. In addition, the data analysis technique used in this study was by making notes on field results that had been carried out, making interview transcripts. Doing triangulation by re-examining the results of data analysis from data collection in the form of observations, interviews. The results of this study are that through learning the art of music with piano media, deaf students at SDLB/B Pangudi Luhur succeeded in playing a song